An experimental approach to climate finance: the impact of auction design and policy uncertainty on renewable energy equity costs in Europe. (October 2019) - Botta, Enrico
Abstract: This paper aims at shedding some lights on how policy induced uncertainty affects the cost of capital of renewable energy power plants. To this end, the paper focuses on renewable energy auctions and on the ongoing Brexit negotiations. First, the paper reviews auction frameworks across Europe and discusses the impact of the different designs on project risk. Then, a stated preference approach is leveraged to investigate how policy design and the uncertainty regarding the future arrangements between the UK and the EU contribute to determine the cost of equity for renewable energy. The results show that improved auction design can help to lower the equity cost between 0.5% and 1.5%. The evidence on Brexit is rather weak and - if anything - suggests only a higher relevance of these negotiations for English-based investors than for those based in EU27. Highlights: Improved auction design can help to lower the equity cost between 0.5% and 1.5%. Adoption of moderate financial bid-bonds drives the highest cost reduction. Trade-offs between different policy objectives need to be carefully assessed.